2018
DOI: 10.1002/pmh.1420
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between effortful control and facets of mindfulness in meditators, non‐meditators and individuals with borderline personality disorder

Abstract: As dimensions of effortful control (EC), activation control, attentional control, and inhibitory control could mediate the relationship between mindfulness meditation practice and the facets of mindfulness (i.e., observing, describing, acting with awareness, non-judging and non-reacting to inner experience). In this study, we tested whether participant status: meditators (n = 330), healthy non-meditators (n = 254) and individuals with borderline personality disorder (BPD) diagnosis (n = 46) predicted the facet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 46 publications
0
6
0
Order By: Relevance
“…For several PD, BIS and EC interacted: BIS was only related to severe PD pathology if EC was low. Another study found low EC in relation to borderline PD [99]. In an earlier study, De Panfilis et al [100] showed a specific role for EC as a mediator between rejection sensitivity and its subsequent interpersonal distress on borderline personality features in an adult community sample, suggesting that low SR capacities may enhance interpersonal distress in response to rejection.…”
Section: Discussionmentioning
confidence: 91%
“…For several PD, BIS and EC interacted: BIS was only related to severe PD pathology if EC was low. Another study found low EC in relation to borderline PD [99]. In an earlier study, De Panfilis et al [100] showed a specific role for EC as a mediator between rejection sensitivity and its subsequent interpersonal distress on borderline personality features in an adult community sample, suggesting that low SR capacities may enhance interpersonal distress in response to rejection.…”
Section: Discussionmentioning
confidence: 91%
“…Research has shown an association between BPD and deficits in mindfulness. For instance, individuals with BPD show lower levels of mindfulness than community (Nicastro, Jermann, Bondolfi, & McQuillan, 2010; Tortella-Feliu et al, 2018) and college samples (Baer, Smith, & Allen, 2004). Furthermore, lower levels of mindfulness are associated with higher BPD features, even after controlling for neuroticism, emotion regulation, and interpersonal effectiveness (Wupperman, Neumann, & Axelrod, 2008; Wupperman, Neumann, Whitman, & Axelrod, 2009).…”
Section: Mechanism Of Change In Dbtmentioning
confidence: 99%
“…A higher level of meditation practice indicated a lower level of borderline symptoms. This finding was endorsed by a related study in that the effortful control of mindfulness meditation was lower among individuals with borderline personality disorder symptoms [ 45 ]. The fact that meditation has two buffering effects on borderline personality disorder symptoms and depression may be related to emotional control and regulatory practices.…”
Section: Discussionmentioning
confidence: 59%